please solve faster if you are topper
Attachments:
![](https://hi-static.z-dn.net/files/dd4/51ad8dbc460fc44044317a62badef532.jpg)
Answers
Answered by
2
Option (b).
Hope it helps you.
Plz mark me as the brainliest.
Hope it helps you.
Plz mark me as the brainliest.
Anonymous:
Wrong answer is 3.....i.e option (c)..
Answered by
1
Answer:
Step-by-step explanation:
f(x) =e^x. g(x)
f'(x)=e^x.g(x) + g'(x).e^x
Put x=0:-
Then f'(0)=e^0.g(0) + g'(0).e^0
=1.2 + 1.1
=3
Answered by an IIT JEE ASPIRANT.......
Similar questions
Political Science,
7 months ago
English,
1 year ago
English,
1 year ago
Math,
1 year ago
History,
1 year ago